The spillover effect of midwife attrition from the Nigerian midwives service scheme - Daniel O. Erim; Harrison E. Offiong; Christine Kim; Folasade A. Bello; Jeremy Moulton; Stephanie B. Wheeler; Harsha Thirumurthy (BMC, 2018)
Abstract Background The Nigerian Midwives Service Scheme (MSS) increased use of antenatal services at rural public sector clinics. However, it is unclear if women who would not have otherwise sought care, or those who would have sought care in rural private sector clinics caused this change. Additionally, it is also unclear if the reported midwife attrition was associated with a spillover of the scheme's effect on urban areas. We sought to answer these two questions using data from two nationally representative surveys. Methods We used an interrupted time series model to assess trends in the use of obstetric (i.e. antenatal and delivery) services among rural and urban respondents in the 2008 and 2013 Nigerian demographic and health surveys. Results We found that the MSS led to a 5-percentage point increase in the use of antenatal services at rural public sector clinics, corroborating findings from a previous study. This change was driven by women who would not have sought care otherwise. We also found that there was a 4-percentage point increase in the use of delivery services at urban public sector clinics, and a concurrent 4-percentage point decrease in urban home deliveries. These changes are most likely explained by midwives' attrition and exemplify a spillover of the scheme's effect. Conclusion Midwife attrition from the Nigerian MSS was associated with a spillover of the scheme's effect on the use of delivery services, on urban areas.